Ethosomes and Transethosomes as Cutaneous Delivery Systems for Quercetin: A Preliminary Study on Melanoma Cells - Francesca Ferrara; Mascia Benedusi; Maddalena Sguizzato; Rita Cortesi; Anna Baldisserotto; Raissa Buzzi; Giuseppe Valacchi; Elisabetta Esposito (MDPI AG, 2022)
The present study is aimed to design ethosomes and transethosomes for topical administration of quercetin. To overcome quercetin low bioavailability, scarce solubility and poor permeability that hamper its pharmaceutical use, the drug was loaded in ethosomes and transethosomes based on different concentrations of phosphatidylcholine. Vesicle morphology was studied by cryogenic transmission electron microscopy, while size distribution and quercetin entrapment capacity were evaluated up to 3 months, respectively, by photon correlation spectroscopy and high-performance liquid chromatography. The antioxidant property was studied by photochemiluminescence test. Quercetin release and permeation was investigated in vitro, using Franz cells associated to different membranes. In vitro assays were conducted on human keratinocytes and melanoma cells to study the behavior of quercetin-loaded nano-vesicular forms with respect to cell migration and proliferation. The results evidenced that both phosphatidylcholine concentration and quercetin affected the vesicle size. Quercetin entrapment capacity, antioxidant activity and size stability were controlled using transethosomes produced by the highest amount of phosphatidylcholine. In vitro permeation studies revealed an enhancement of quercetin permeation in the case of transethosomes with respect to ethosomes. Notably, scratch wound and migration assays suggested the potential of quercetin loaded-transethosomes as adjuvant strategy for skin conditions.